2013
DOI: 10.1111/ajr.12014
|View full text |Cite
|
Sign up to set email alerts
|

Improving eye care for Indigenous Australians in primary health care settings

Abstract: Background: This paper aims to assess the barriers and solutions to the delivery of eye care in primary care settings and solutions to improve the use of comprehensive eye care among Indigenous Australians. Design, setting, participants: Qualitative, mixed method study participants include Aboriginal community members, and health and eye care providers in urban, rural and remote settings. Main outcome measures: Present evidence for health care providers to better understand and address some of the barriers tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 12 publications
1
24
0
Order By: Relevance
“…Our study indicates that the provision of health literacy on chronic wet cough will be a vital enabler to facilitating health seeking. Our findings are consistent with previous studies on middle ear and eye diseases, which found that Aboriginal people would seek help earlier if they had recognised and understood that their child was sick . An important barrier to health seeking for many parents was that key health messages about chronic wet cough in children had previously not been communicated by health staff.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study indicates that the provision of health literacy on chronic wet cough will be a vital enabler to facilitating health seeking. Our findings are consistent with previous studies on middle ear and eye diseases, which found that Aboriginal people would seek help earlier if they had recognised and understood that their child was sick . An important barrier to health seeking for many parents was that key health messages about chronic wet cough in children had previously not been communicated by health staff.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings are consistent with previous studies on middle ear and eye diseases, which found that Aboriginal people would seek help earlier if they had recognised and understood that their child was sick. 18,22 An important barrier to health seeking for many parents was that key health messages about chronic wet cough in children had previously not been communicated by health staff. The significance of chronic wet cough may not yet be well understood by many health practitioners and even less by the general public because PBB, the most common cause of chronic wet cough in children in Australia, 23 was only officially recognised by the Thoracic Society of New Zealand and Australia in 2006 21 and by the British Thoracic Society in 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen of the eighteen studies clearly described the target population and the goals of the effort. Boudville and colleagues detailed both of these principles as they evaluated access to eye care in a primary care setting in Aboriginal communities[15]. Their qualitative, mixed method study used knowledge of the community to further elucidate the role of primary care providers in eye health.…”
Section: Resultsmentioning
confidence: 99%
“…Our results are significantly less than this, and this would seem to reflect the failure to record in the clinical records the trachoma examinations conducted by the jurisdictional trachoma screening programs. Improved coordination between external trachoma screening services and PHC centers will enable PHC centers to continue to make a significant contribution toward closing the gap for vision in Australia (9). …”
Section: Discussionmentioning
confidence: 99%
“…Hence, PHC centers play a crucial role in eye care (9), especially for patients with diabetes (7). Basic eye and vision screening assessments are conducted during routine health assessments such as the Aboriginal and Torres Strait Islander Health Assessment (10).…”
Section: Introductionmentioning
confidence: 99%